DEFINITION OF PRESSURE INTRAMYOCARDIAL AS A METHOD FOR EVALUATING MORPHOFUNCTIONAL STATE STRUCTURE OF THE HEART AT DIFFERENT STAGES OF ONTOGENESIS - V. Y. Lebedinsky; Yu. A. Visotskiy; G. N. Borodina (Acta Biomedica Scientifica, 2012)
Intramyocardial pressure structures of the heart is determined by qualitative and. quantita-tive characteristics of its constituent structural elements. Correlation analysis revealed that the formation of stress-strain states in addition to cardiomyocytes affect fibers of connective tissue.